THE MEANING OF PUBLIC POLICY UNDER INDONESIAN ARBITRATION LAW AND PRACTICE - Adolf, Huala (Transnational Business Law Journal, 2021)
This article tried to see the meaning of public policy under Indonesian arbitration law. The arbitration law examined was the arbitration law in the Code of Civil Procedures of 1847, the Presidential Decree No 34 of 1981, the Supreme Court Regulation No 1 of 1990 and the Arbitration law No 30 of 1999. The article also took a closer look on Indonesian court in interpreting the term public policy in its decisions. The method used in this article was descriptive-analytical. The data was in particular the decisions of the courts of Indonesia including Domestic Court, High Court and Supreme Court. A comparative study was taken, describing the arbitration acts of certain countries in particular New Zealand, Malaysia and Fiji. This article concluded, as cases developed, the approach toward public policy was the strict application of it. This article also recommended the amendment of the arbitration law by including the indicators as to what the public policy would cover as found in arbitration acts of states being studied.